Psychophysiological stress response after a 6-week Mindful Self-Compassion training in psychiatric rehabilitation inpatients: a randomized post-test only study - Andorfer, Andrea; Kraler, Sabina; Kaufmann, Paul; Pollheimer, Ewald; Spah, Christoph; Fuchshuber, Jürgen; Rominger, Christian; Traunmüller, Claudia; Schwerdtfeger, Andreas; Unterrainer, Human-Friedrich (Frontiers in Psychiatry, 2023)
Objectives Mindfulness-based interventions (including self-compassion interventions) are effective in improving stress management at psychological and physical levels. Mindful Self-Compassion (MSC) is a newly developed program particularly aimed at increasing self-compassion. The main objective of this study was to determine whether the psychophysiological stress response during a social-evaluative speaking task differs in inpatients participating in the MSC or the Progressive Muscle Relaxation (PMR) program at the end of their 6-week psychiatric rehabilitation stay (i.e., post-test only design). Method Data from 50 inpatients (25 MSC, 25 PMR, 35 female) aged 19 to 76 years (M = 47.22, SD = 12.44) were analyzed in terms of psychophysiological stress response. For this purpose, heart rate variability, heart rate, and blood pressure were assessed together with several psychometric variables: positive and negative affect (PANAS), subjective stress perception (Visual Analog Scale), self-compassion (Self-Compassion Scale), cognitive reappraisal and suppression (Emotion Regulation Questionnaire), psychological distress (Brief Symptom Inventory-18), and appraisal and rumination (selected items). Results After correction for alpha inflation no differences in the psychophysiological stress response and psychometric parameters between the MSC and PMR group were found. Discussion In general, our results indicate that MSC is not superior to PMR training. However, more research with clinical randomized controlled trials investigating larger samples are needed to further affirm these initial findings.